Signaling via class IA Phosphoinositide 3-kinases (PI3K) in human, breast-derived cell lines. - Veronique Juvin; Mouhannad Malek; Karen E Anderson; Carine Dion; Tamara Chessa; Charlotte Lecureuil; G John Ferguson; Sabina Cosulich; Phillip T Hawkins; Len R Stephens (PLoS ONE)
We have addressed the differential roles of class I Phosphoinositide 3-kinases (PI3K) in human breast-derived MCF10a (and iso-genetic derivatives) and MDA-MB 231 and 468 cells. Class I PI3Ks are heterodimers of p110 catalytic (α, β, δ and γ) and p50-101 regulatory subunits and make the signaling lipid, phosphatidylinositol (3,4,5)-trisphosphate (PtdIns(3,4,5)P3) that can activate effectors, eg protein kinase B (PKB), and responses, eg migration. The PtdIns(3,4,5)P3-3-phosphatase and tumour-suppressor, PTEN inhibits this pathway. p110α, but not other p110s, has a number of onco-mutant variants that are commonly found in cancers. mRNA-seq data shows that MCF10a cells express p110β>>α>δ with undetectable p110γ. Despite this, EGF-stimulated phosphorylation of PKB depended upon p110α-, but not β- or δ- activity. EGF-stimulated chemokinesis, but not chemotaxis, was also dependent upon p110α, but not β- or δ- activity. In the presence of single, endogenous alleles of onco-mutant p110α (H1047R or E545K), basal, but not EGF-stimulated, phosphorylation of PKB was increased and the effect of EGF was fully reversed by p110α inhibitors. Cells expressing either onco-mutant displayed higher basal motility and EGF-stimulated chemokinesis.This latter effect was, however, only partially-sensitive to PI3K inhibitors. In PTEN(-/-) cells, basal and EGF-stimulated phosphorylation of PKB was substantially increased, but the p110-dependency was variable between cell types. In MDA-MB 468s phosphorylation of PKB was significantly dependent on p110β, but not α- or δ- activity; in PTEN(-/-) MCF10a it remained, like the parental cells, p110α-dependent. Surprisingly, loss of PTEN suppressed basal motility and EGF-stimulated chemokinesis. These results indicate that; p110α is required for EGF signaling to PKB and chemokinesis, but not chemotaxis; onco-mutant alleles of p110α augment signaling in the absence of EGF and may increase motility, in part, via acutely modulating PI3K-activity-independent mechanisms. Finally, we demonstrate that there is not a universal mechanism that up-regulates p110β function in the absence of PTEN.